4CPS-121 Emergency medicine clinical pharmacist's interventions and their impact on preventable adverse drug events. (23rd March 2022) - Garreta, G; Sebastian, C; Iglesias, M; Salazar, F; Meca, N; Pardo, J; Sangrador, C; Nicolas, J
Abstract : Background and importance: Emergency departments (ED) with established emergency pharmacist programmes have reported on both cost savings and a perception among physician and nursing staff that medication safety and quality of care are improved. Thence, in ED, the involement of clinical pharmacists can play an important part in the identification and reduction of preventable adverse drug events (ADEs). Aim and objectives: Evaluate the type and frequency of an emergency medicine (EM) clinical pharmacist's intervention (CPI) on physicians' prescribing and their effect on preventable ADEs. Analyse the acceptance of CPI. These interventions were related to identifying, preventing and resolving drug-related problems. Material and methods: Retrospective observational study of all CPI completed on ED lodged (inpatient) adult (≥16 years old) prescriptions over 4 months in an academic hospital of 400 beds. The National Coordinating Council for Medication Error Reporting and Prevention (NCC MERP) Index for Categorising Medication Errors Algorithm was used to categorise interventions. An ADE has been defined as "any harm associated with any dose of a drug". Results: A total of 645 CPI were collected in 607 patients (mean average of 1.23±1.89 CPI per patient). Mean age was 77±10.4 years and 69% were men. The acceptance rate was 90.4%; all CPI were conducted face-to-face with a physician. CPI most often pertained to anti-infective agents (40%), cardiovascular agents (17%), insulin (10%) and anticoagulants and thrombolytics (10%). The predominant intervention type were dose adjustment (35%), omission of regular medication on admission (30, 5%), therapeutic substitutions(30%), initiating drug therapy(16.5%) and changes in route of drug administration (11%). Of overall CPI, 42% were categorised as potential ADEs. The most common preventable ADEs intercepted were improper dose (56%) and frequency and route (23%). The most common outcomes for interventions were reduction of preventable ADEs (45%) and optimisation of the therapeutic effects of the drugs that were administered (29%). Conclusion and relevance: This study demonstrated that adding EM pharmacists to the ED decreased significantly the rate of medication errors and potenital ADEs. Also, working side-by-side would explain the good acceptance of the CPI by ED physicians. However, further study is needed to demonstrate the clinical pharmacist's contribution to the improvement of clinical and economic outcomes more comprehensively. References and/or acknowledgements: Conflict of interest: No conflict of interest